1996
DOI: 10.1007/bf00641312
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 8 preceding diagnosis of acute nonlymphocytic leukemia by 2 years in a patient with multiple myeloma without cytological evidence of myelodysplasia

Abstract: A case of acute nonlymphocytic leukemia (ANLL) occurring 2 years after the diagnosis of multiple myeloma (MM) that had been treated by only one course of melphalan/prednisone chemotherapy is reported. Cytogenetic and fluorescence in situ hybridization analysis of peripheral blood cells revealed trisomy 8 as the sole cytogenetic defect at the time of diagnosis of ANLL. Two years earlier, when MM was diagnosed without any cytological evidence of co-existent myelodysplasia, chromosomal analysis of bone marrow cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Several investigations (Rö djer et al, 1990;Merlat et al, 1999;Mauritzson et al, 2002;Pedersen-Bjergaard et al, 2002;Smith et al, 2003) have shown that myeloid malignancies post-MM are characterized by cytogenetic patterns typical of alkylating agent-induced MDS/ AML, that is, complex karyotypes, hypodiploidy, and certain genomic aberrations, for example, total or partial loss of chromosomes 5, 7, and 17, deletions of 12p, and monosomy 18 (Table 1). Although the presence of these cytogenetic features in MM, sometimes occurring without any signs of MDS/ AML (Dewald et al, 1985;Clark et al, 1989;Johansson et al, 1995;Weh et al, 1996;Amiel et al, 1999;Fonseca et al, 2000;Blann et al, 2002;Ferro et al, 2002), often indicates an emerging malignant myeloid disorder, in particular, if the MM patient has received alkylating therapy, the interpretation of such karyotypic findings can be difficult in individual cases. For this reason, we performed statistical analyses of all cytogenetically abnormal MMs and t-MDS/t-AMLs post-MM reported in the literature (Mitelman et al, 2004) in order to identify genomic patterns that could be used to distinguish between these two disease entities.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several investigations (Rö djer et al, 1990;Merlat et al, 1999;Mauritzson et al, 2002;Pedersen-Bjergaard et al, 2002;Smith et al, 2003) have shown that myeloid malignancies post-MM are characterized by cytogenetic patterns typical of alkylating agent-induced MDS/ AML, that is, complex karyotypes, hypodiploidy, and certain genomic aberrations, for example, total or partial loss of chromosomes 5, 7, and 17, deletions of 12p, and monosomy 18 (Table 1). Although the presence of these cytogenetic features in MM, sometimes occurring without any signs of MDS/ AML (Dewald et al, 1985;Clark et al, 1989;Johansson et al, 1995;Weh et al, 1996;Amiel et al, 1999;Fonseca et al, 2000;Blann et al, 2002;Ferro et al, 2002), often indicates an emerging malignant myeloid disorder, in particular, if the MM patient has received alkylating therapy, the interpretation of such karyotypic findings can be difficult in individual cases. For this reason, we performed statistical analyses of all cytogenetically abnormal MMs and t-MDS/t-AMLs post-MM reported in the literature (Mitelman et al, 2004) in order to identify genomic patterns that could be used to distinguish between these two disease entities.…”
Section: Discussionmentioning
confidence: 97%
“…In most instances, such cytogenetic features signify the presence of therapyrelated malignancies, in particular, t-MDS/t-AML in MM patients who have previously been treated with alkylating agents (Rö djer et al, 1990;Merlat et al, 1999;Pedersen-Bjergaard et al, 2002). In a few instances, however, MDS/AML-associated chromosomal changes, for example, der(1;7)(q10; p10), t(1;3)(p36;q21), del(5q), Ϫ7, ϩ8, and del(20q), are detected in PCDs without any morphologic features of MDS or AML (Dewald et al, 1985;Clark et al, 1989;Johansson et al, 1995;Weh et al, 1996;Amiel et al, 1999;Fonseca et al, 2000;Blann et al, 2002;Ferro et al, 2002). The clinical significance of these aberrations has not been investigated in any greater detail.…”
Section: Introductionmentioning
confidence: 97%
“…AML than in plasma cell neoplasms. In MM trisomy 8 usually indicates development of a therapy-related myeloid neoplasm, or a concurrent myeloproliferative neoplasm [36][37][38]. Identification of specific trisomies is important in the distinction of hyperdiploidy of MM from those occurring in AML.…”
Section: Discussionmentioning
confidence: 99%
“…Robak et al [ 17 ]reported a rare case of primary PCL with trisomy 8. Additionally, an MM patient with trisomy 8 was reported to develop nonlymphocytic leukemia with the same karyotypic abnormality as the preexisting myeloma cells [ 18 ]. However, no cases of secondary PCL with trisomy 8 have previously been reported.…”
Section: Discussionmentioning
confidence: 99%